Correlation of Hemorrhage Near Developing Opossum Skull With Pulsed Ultrasound Exposure Parameters. (1st August 2015) - Kumar, Viksit; Bigelow, Timothy A.; Mullin, Kathleen; Sakaguchi, Donald S.
Abstract : Objectives: High‐intensity focused ultrasound (HIFU) has been used noninvasively for therapeutic applications. Before HIFU can be used therapeutically on a human fetus, the bioeffects related to HIFU must be studied, and the mechanism causing the bioeffects should be understood. Previous studies have shown that HIFU, when targeted on fetal rat and mice bones. resulted in hemorrhage. However, the mechanism responsible has not been identified. In this study, we looked at ultrasound parameters related to hemorrhage in an effort to better understand the mechanism. Methods: Brazilian opossum pups (7–8 postnatal days) were exposed to a 1.1‐MHz f/1 spherically focused transducer (6.3 cm focal length). Four treatment groups of n = 14 and a control group of n = 14 were exposed to rarefactional pressures of 3.6 to 6 MPa with spatial‐peak temporal average intensity values of 5.4 to 10.8 W/cm 2 . The pulse repetition frequency was varied from 500 to 1000 Hz with exposure durations of 1 to 4 minutes. Results: Four groups with sample sizes of 14 had hemorrhage percentages of 43%, 36%, 29%, and 36%, respectively. Hemorrhage occurrence and size were found to correlate strongly with the nonlinear product of energy density and number of pulses, with correlation values of 0.92 and 0.97, respectively. Conclusions: The dependence of hemorrhage on energy density and the number of pulses suggests that the hemorrhage may be due to high‐stress, low‐cycle mechanical fatigue damage. Hence, for therapeutic applications, the product of energy density and number of pulses should not exceed a certain predetermined limit.